Posyandu Roles as Mothers and Child Health Information Center - Saepuddin, Encang; Rizal, Edwin; Rusmana, Agus (Record and Library Journal, 2017)
This research studied on The Posyandu Roles as Mothers and Children Health Information Center in Narawita Village Cicalengka County Bandung Regency. With objectives to find out community perceptions toward the Posyandu (center of integrated health services) Programs, its roles in improving health quality of mothers and children, and the Posyandu as an information center for communities, this study used qualitative method and data are gathered through interviews, observations, focus group discussion, and a literature study. The respondents are Posyandu cadres, the Village PKK (family welfare program) cadres, medical practitioners, and the posyandu members. The results show that the communities perceptions toward Posyandu Programs are adequately positive, Posyandu has important roles in improving the health of mothers and children through health service processes, and Posyandu has became as a community health information center.